The presidential papers of Ramon Magsaysay a plan for their organization, administration and development - Nivera, Pat I. (1971)
Records act as the tangible memory of nations, organizations and individuals. These are generally classified into textual, pictorial and cartographic records. The records created by and for the President of the Philippines, better known as his Papers, reflect much of his own actuations, the state of the country at a given period and the nation's international position. As such, they are valuable sources for the writing of political, socio-economic or diplomatic history, for biographies; for the documentation of events or for tracing the course of public administration and government machinery.